2015
DOI: 10.5935/1678-9741.20150054
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation (TAVI) with balloon-expandable valve: early experience from China

Abstract: ObjectiveThe aim of the current study was to evaluate the early experience of the application of transcatheter aortic valve implantation with the balloon-expandable system in China. The transcatheter aortic valve implantation technology has been widely used for patients with inoperable severe aortic stenosis in the developed world. The application of transcatheter aortic valve implantation is still in the early stages of testing in China, particularly for the balloon-expandable valve procedure.MethodsThis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Recently, the new generation of the balloon-expandable valve system has shown less occurrence of aortic regurgitation and pacemaker implantation [ 22 ] . This cohort had clinical endpoints and complications defined by VARC-2 [ 23 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the new generation of the balloon-expandable valve system has shown less occurrence of aortic regurgitation and pacemaker implantation [ 22 ] . This cohort had clinical endpoints and complications defined by VARC-2 [ 23 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter aortic valve implantation (TAVI) is a new treatment option that is primarily applied in high-risk patients and is suggested to be applied for moderate and low risk afterwards [ 3 ] . Lu et al [ 4 ] demonstrated a significant improvement in the valve functions and New York Heart Association classification after TAVI procedure in a small group of patients over 75 years old. In another study by Kocaaslan et al, the increase in quality of life parameters measured with the 36-Item Short Form Survey, or SF-36, in the TAVI group at the end of the 3 rd postoperative month was greater than that in the AVR group [ 5 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Transcatheter aortic valve implantation (TAVI) was initially introduced by Cribier and colleagues and, currently, TAVI represents a valid therapeutic option for patients with severe aortic stenosis who are inoperable or are at very high risk for conventional surgery [ 1 , 2 ] . TAVI is performed using one of two different approaches: the retrograde transfemoral (TF) approach via the femoral artery or the antegrade transapical (TA) [ 3 ] .…”
Section: Introductionmentioning
confidence: 99%